Poverty reduction, inequalities and human development in the BRICS: policies and outcomes - Maiorano, Diego; Manor, James (Taylor and Francis, 2017)
This paper assesses headway made by governments in Brazil, India, China and South Africa in pursuing three goals: reducing income poverty; reaching the poorest of the poor; and reducing inequality. Outcomes vary as we move up the ladder from the first and easiest of these challenges to the third and most daunting. Then the definition of poverty is broadened to include severe shortage of opportunities, liberties and capabilities. The paper discusses how the four countries performed in ameliorating several human development indicators and in enhancing poor people’s ‘political capacity’, the lack of which is an important dimension of their poverty.